2017
DOI: 10.18632/oncotarget.18521
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic and diagnostic value of circulating tumor cells in bladder cancer and upper tract urothelial carcinoma: a meta-analysis of 30 published studies

Abstract: There are inconsistent conclusions in the association between circulating tumor cells (CTCs) and urothelial cancer (UC). We performed a meta-analysis to assess the prognostic and diagnostic value of CTCs in UC. We search Medline, Embase and Web of science for relevant studies. The study was set up according to the inclusion/exclusion criteria. 30 published studies with a total of 2161 urothelial cancer patients were included. Meta-analysis showed that CTC-positive was significantly associated with tumor stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 47 publications
(30 reference statements)
3
41
0
1
Order By: Relevance
“…There is general agreement that by adding biomarkers that reflect the biologic behavior of HGT1 bladder cancer to established parameters in nomograms, significant improvements in risk stratification could be achieved. Strategies to identify putative biomarkers in liquid biopsies from blood and urine collected from patients with bladder cancer are being developed to monitor subclinical systemic disease and to identify candidate targets for therapeutic intervention . Circulating tumor cells (CTCs), in particular, are regarded as surrogate for early dissemination of disease and have been qualified as accurate prognostic biomarkers in different cancer types, including bladder cancer .…”
Section: Introductionmentioning
confidence: 99%
“…There is general agreement that by adding biomarkers that reflect the biologic behavior of HGT1 bladder cancer to established parameters in nomograms, significant improvements in risk stratification could be achieved. Strategies to identify putative biomarkers in liquid biopsies from blood and urine collected from patients with bladder cancer are being developed to monitor subclinical systemic disease and to identify candidate targets for therapeutic intervention . Circulating tumor cells (CTCs), in particular, are regarded as surrogate for early dissemination of disease and have been qualified as accurate prognostic biomarkers in different cancer types, including bladder cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Although inconsistent results with regard to the association between the clinicopathological features and the presence of CTCs in patients with UCB have been reported [16][17][18][19][20][21], the association between the detection of CTCs and poor oncological outcomes of UCB patients has already been confirmed by a variety of studies [18][19][20]22]. Recently, a systemic review study regarding the association between CTC-positive results and the clinicopathological features and prognostic outcomes in 2161 patients with UCB showed that the presence of CTCs in the peripheral blood was an independent predictive indicator of both poor histopathological parameters and poor oncological outcomes [23]. Furthermore, in the first report regarding the presence of CTCs in NMIBC patients using CellSearch, Gazzaniga et al showed that the detection of CTCs was significantly associated with both poor histopathological parameters and poor oncological outcomes [18].…”
Section: Discussionmentioning
confidence: 90%
“…A recent meta-analysis assessed a total of 2161 BC patients at different disease stages, correlating the presence of CTCs with tumor stage, histological grade, regional lymph node metastasis, and metastases, indicating that CTCs are more easily detected in more advanced stages of BC. Furthermore, patients CTC-positive versus CTC-negative exhibited poorer cancer specific survival, PFS, disease-free survival, and OS [ 71 ]. Along this line, CTC assessment using the CellSearch System in 33 patients with metastatic UC underlined a higher number of CTCs in patients with more than two metastatic sites compared to those with <1 metastatic site [ 72 ].…”
Section: Bladder Cancermentioning
confidence: 99%